(untitled) - Calitz, Jacques

Analysis of the Hydrodynamics of rectangular plunging Jets and the subsequent scouring in broken-up Rock Beds (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.